Sustainable land management - a Caribbean perspective - Bishop, Andrew R. (2009)
Posits that the political will to adopt sustainable land management and land use planning into annualised internally funded programmes is the biggest challenge that countries face. Adds that donor driven activities will only be effective if it is accompanied by a strong domestic will and tangible commitment.